2007
DOI: 10.1002/bit.21331
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting the pressure effect on lipase‐catalyzed wax ester synthesis in dense carbon dioxide

Abstract: The present work focuses on the thermodynamic interpretation of the lauryl oleate biosynthesis in high-pressure carbon dioxide. Lipase-catalyzed lauryl oleate production by oleic acid esterification with 1-dodecanol over immobilized lipase from Rhizomucor miehei (Lipozyme RM IM) was successfully performed in a sapphire window batch stirred tank reactor (BSTR) using dense CO(2) as reaction medium. The experiments were planned to elucidate the pressure effect on the reaction performance. With increasing the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…However, a similar result was also reported in a study of lavandulol esterification [26]. On the other hand, Knez et al and Laudani et al [14,16] demonstrated the highest degree of wax ester synthesis is at 10 MPa, and that if the pressure was out of the range 8. 27-12.41 MPa the degree of esterification significantly decreased.…”
Section: Model Fittingsupporting
confidence: 60%
See 2 more Smart Citations
“…However, a similar result was also reported in a study of lavandulol esterification [26]. On the other hand, Knez et al and Laudani et al [14,16] demonstrated the highest degree of wax ester synthesis is at 10 MPa, and that if the pressure was out of the range 8. 27-12.41 MPa the degree of esterification significantly decreased.…”
Section: Model Fittingsupporting
confidence: 60%
“…Several detailed review papers on enzymatic reactions in supercritical fluids (SCF) have been reported and published [12,13]. Enzymatic synthesis of wax esters in SC-CO 2 is organic solvent-free, with the extra advantages of easy separation of unreacted substances, high diffusivity, low viscosity, and low surface tension [14,15]. There have been a few studies regarding lipase-catalyzed synthesis of wax esters in SC-CO 2 .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The positive effect can be related to the increase of CO 2 density with pressure, which improves its solvation power in the reaction medium [20]. In turn, the negative effect on the conversion can be connected with the dilution of the substrates caused by the greater amount of CO 2 pumped into the reactor, causing an increase in the molar ratio between SC-CO 2 and substrates [20,38]. Knez et al [38] studied the effect of pressure on the conversion of free fatty acid into fatty acid ester using lipase from Rhizomucor miehei (Lipozyme RM IM) in dense CO 2 .…”
Section: Effect Of Pressure and Temperature Of Sc-comentioning
confidence: 97%
“…Dodecyl oleate is a wax ester that has lubricant, pharmaceutical and cosmetic applications (Knez et al 2007). Because wax esters are usually water-insoluble, like dodecyl oleate, we believe that it is possible to use a variety of wax ester synthesis reactions for the lipase and esterase zymography.…”
Section: Discussionmentioning
confidence: 99%